THU0567 Rapid improvement with tocilizumab in refractory and severe uveitic cystoid macular edema. (15th June 2017) - Vegas-Revenga, N; Calvo-Río, V; Palmou-Fontana, N; Mesquida, M; Adan, A; Hernández, M; Beltrán, E; Valls, E; Díaz-Valle, D; Díaz-Soriano, G; Hernández-Grafella, M; Martínez-Costa, L; et al.
Abstract : Background: In uveitis, remission-inducing therapy with even more vigor than does rheumatology is mandatory. Since the eye is so much less forgiving of chronic inflammation than is the joint, with profound life-altering consequences. Cystoid macular edema (CME) is the leading cause of blindness in uveitis. Objectives: To evaluate the rapid efficacy of Tocilizumab (TCZ) in refractory CME. Methods: Multicentre study of 25 patients with CME due to non-infectious uveitis who had inadequate response to traditional treatment with corticosteroids and at least one conventional immunosuppressive drug including in most cases biological therapy (n=22). CME was defined as OCT >300 μm. The outcome variables were the degree of inflammation, visual acuity, macular thickness. The results are expressed as mean±SD for normally distributed variables, or as median [IQR] when are not. Comparison of continuous variables was performed using the Wilcoxon test. Results: 25 patients (17 women/8 men), mean age 33.6±18.9 years were studied. The associated diseases were: juvenile idiopathic arthritis (9), Behçet's (7), Birdshot (4), idiopathic (4), sarcoidosis (1). The ocular pattern was: panuveitis (9), anterior uveitis (7), posterior uveitis (5) and intermediate uveitis (4). Most patients had bilateral involvement (24). Prior to TCZ they received: intraocular corticosteroids (22), iv. methylprednisolone (7), methotrexate (MTX) (19), cyclosporine A (CSA) (17), mycophenolate (4), azathioprine (2), leflunomide (2), cyclophosphamide (1), sulfasalazine (1), acetazolamide (1) and thalidomide (1). The biological used before TCZ were infliximab (8), adalimumab (19), etanercept (2), golimumab (2), rituximab (2), abatacept (3), anakinra (1) and daclizumab (1). TCZ administration schedule was 8 mg/kg/4 weeks iv. (n=23), every 2 weeks (1) and subcutaneously 162 mg/2 weeks (1). TCZ was used in monotherapy (13) or combined with conventional immunosuppressive drugs (12). Most of intraocular inflammation parameters showed a rapid improvement after TCZ onset (Table), with corticosteroid-sparing effect (15.9±13.6 to 8.5±5.17 mg; p=0.001). Remission was achieved in 8 patients and improvement in 17. After one month of therapy, no side effects were observed. Conclusions: TCZ seems a rapid effective treatment in refractory uveitic CME. Disclosure of Interest: None declared